Serotonergic Modulation of Conditioned Fear. (24th October 2012) - Homberg, Judith R.
Abstract : Conditioned fear plays a key role in anxiety disorders as well as depression and other neuropsychiatric conditions. Understanding how neuromodulators drive the associated learning and memory processes, including memory consolidation, retrieval/expression, and extinction (recall), is essential in the understanding of (individual differences in vulnerability to) these disorders and their treatment. The human and rodent studies I review here together reveal, amongst others, that acute selective serotonin reuptake inhibitor (SSRI) treatment facilitates fear conditioning, reduces contextual fear, and increases cued fear, chronic SSRI treatment reduces both contextual and cued fear, 5-HT1A receptors inhibit the acquisition and expression of contextual fear, 5-HT2A receptors facilitates the consolidation of cued and contextual fear, inactivation of 5-HT2C receptors facilitate the retrieval of cued fear memory, the 5-HT3 receptor mediates contextual fear, genetically induced increases in serotonin levels are associated with increased fear conditioning, impaired cued fear extinction, or impaired extinction recall, and that genetically induced 5-HT depletion increases fear conditioning and contextual fear. Several explanations are presented to reconcile seemingly paradoxical relationships between serotonin levels and conditioned fear.